Comparative Analysis Of Two Specialized 3d Resins Tailored For Prosthodontic Applications: An In Vitro Study - Agrawal, Sanjana Suresh; Karpathak, Shilpi; H.G, Jagadeesh; Dhanvijay, Tushar; Agrawal, Sandeep; Sharma, Shashwat (Journal of Neonatal Surgery, 2025)
Introduction: Three-dimensional (3D) printing has become an increasingly popular manufacturing tool in the medical world. Three-dimensional printing allows dentists to create high-precision models of teeth and jaw structure, and enables them to develop customized tools for patient’s treatment. Aim & Objectives: To compare the mechanical properties (compression and tensile moduli) of two commercially available 3D-printable resins (Elegoo and Anycubic) used in dentistry. Material And Methodology: Two 3D-printable resins, namely Elegoo and Anycubic were tested to evaluate their properties and Universal Testing Machine was used for testing their mechanical properties. Both are biocompatible materials, but with different properties. Result: The compressive and tensile strength of Anycubic resin was significantly higher than Elegoo resin. Conclusion: Anycubic 3D resin material is more adequate for use in prosthodontic applications as compare to Elegoo 3D resin material, Anycubic 3D resin could be used more as a stiff material